2000
DOI: 10.1007/s001340000751
|View full text |Cite
|
Sign up to set email alerts
|

Human errors in a multidisciplinary intensive care unit: a 1-year prospective study

Abstract: Critical incidents add morbidity, workload, and financial burden. A substantial proportion of them are related to human factors with dire consequences. Efforts must focus on timely, appropriate care to avoid planning and execution mishaps at the beginning of the ICU stay; surveillance intensity must be maintained, specially after the fourth day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
14

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 14 publications
5
76
0
14
Order By: Relevance
“…14,[16][17][18][19] We found that 36% of adverse events and 6.1% of in-ICU deaths were certainly or probably preventable, in agreement with previously published data. Our analysis also showed that the impact of disease severity at ICU admission on the preventability of events diverged between deaths and adverse events.…”
Section: Timing Of Adverse Eventssupporting
confidence: 92%
See 2 more Smart Citations
“…14,[16][17][18][19] We found that 36% of adverse events and 6.1% of in-ICU deaths were certainly or probably preventable, in agreement with previously published data. Our analysis also showed that the impact of disease severity at ICU admission on the preventability of events diverged between deaths and adverse events.…”
Section: Timing Of Adverse Eventssupporting
confidence: 92%
“…[14][15][16][17][18][19] Nevertheless, data on the rates of adverse events and medical errors in ICUs are contradictory because nosocomial infections and iatrogenic complications due to invasive procedures or medications are not always preventable. 14,17,18 In addition, adverse events are often responsible for patients' being transferred to the ICU, further complicating the analysis of preventability of accidental injuries in ICUs. 19 Therefore, the rates of preventable adverse events per 1000 ICU patient-days are estimated to be between 13 and 40, and in-ICU medical errors could prolong the ICU stay by 15% and increase hospital costs by 10%.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These human errors are frequent and may be associated with high morbidity and mortality. 2,3 An optimal device for emergency care should provide adequate technical performance, combined with optimal ergonomics (ie, an easy-to-use and user-friendly human/machine interface). 4,5 Significant improvement in the technical performance of emergency and transport ventilators has been observed during the last decade, 6 and more recent devices have demonstrated technical performance similar to that of ICU ventilators.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, decision making and safety may be a challenge in routine practice. It has been emphasized that human error is responsible of the majority of medical accidents [6] and that most of these accidents are considered avoidable [7]. In this context, the development of user-machine interfaces specifically designed to facilitate cognitive processes may increase the ease of care giver interactions and reduce the number of accidents.…”
mentioning
confidence: 99%